Experiences of Students with the Implementation of the Theme of Shoah into Teaching - Mašát, Milan (Journal of Education Culture and Society, 2024)
Aim. In this paper, we present selected results of a research survey conducted among teacher education students to determine their preconceptions about the implementation of the events of the Shoah into teaching at different levels of education.Methods. In this paper we answer the following research questions: Would the respondents welcome a greater curricular anchoring of the Shoah in the Framework Curriculum for Primary Education? Are prospective teachers interested in various books on the Shoah in their spare time? What methods and forms of work were used in teaching in connection with the events of the Shoah at the graduated primary school? In which year of primary school do respondents think it is appropriate to include Shoah topics? Are the respondents satisfied with the level of integration of the Shoah phenomenon into teaching at the Faculty of Education of Palacký University in Olomouc?Results. Most respondents believe that the Shoah phenomenon is only suitable for integration at the lower-secondary school. This preconception stems mainly from the respondents´ previous experience in primary schools.Conclusion. The results point to the fact that the transformation of the perception of the defined events, and the related broader possibilities of their application in Czech institutional teaching, will be quite complex.Cognitive value. It is necessary to begin to perceive the Shoah also in a certain transcendental, visceral level and, based on the internalisation of the resulting feelings, to begin to build pupils´ awareness of the importance of democracy, freedom, or tolerance.